2015
DOI: 10.1002/bio.2850
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptional and proteomic survey of Arachnocampa luminosa (Diptera: Keroplatidae) lanterns gives insights into the origin of bioluminescence from the Malpighian tubules in Diptera

Abstract: Fungus-gnats of the genus Arachnocampa are unique among bioluminescent insects for displaying blue-green bioluminescence, and are responsible for one of the most beautiful bioluminescence spectacles on the roofs of the Waitomo Caves. Despite morphological studies showing that Arachnocampa larval lanterns involve specialization of the Malpighian tubules, the biochemical origin of their bioluminescence remains enigmatic. Using a cDNA library previously constructed from lanterns of the New Zealand glowworm A. lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…Amongst the salivary gene families unique to NW sand flies, the c-type lectin, the mannose-binding lectin, and the spider toxin-like gene families share paralogs expressed in other tissues of sand flies and other unrelated arthropods (Abdeladhim et al, 2016). Similar phenomena were noticed for salivary protein families unique to OW sand flies, such as phospholipase A2 (Tunaz et al, 2003) and pyrophosphatase (Silva et al, 2015), as well as in protein families shared with NW sand flies, like hyaluronidase (Allalouf et al, 1975), endonuclease (Broderick et al, 2014), adenosine deaminase (Dolezelova et al, 2005), and OBPs (Benoit et al, 2017). Hence, such gene families seem to have emerged by sub-functionalization.…”
Section: Resultssupporting
confidence: 52%
“…Amongst the salivary gene families unique to NW sand flies, the c-type lectin, the mannose-binding lectin, and the spider toxin-like gene families share paralogs expressed in other tissues of sand flies and other unrelated arthropods (Abdeladhim et al, 2016). Similar phenomena were noticed for salivary protein families unique to OW sand flies, such as phospholipase A2 (Tunaz et al, 2003) and pyrophosphatase (Silva et al, 2015), as well as in protein families shared with NW sand flies, like hyaluronidase (Allalouf et al, 1975), endonuclease (Broderick et al, 2014), adenosine deaminase (Dolezelova et al, 2005), and OBPs (Benoit et al, 2017). Hence, such gene families seem to have emerged by sub-functionalization.…”
Section: Resultssupporting
confidence: 52%
“…Malpighian tubules are also capable of secreting silk-like substances. This 'malpighian silk' has been observed in Neuroptera, Coleoptera and Hymenoptera [Sutherland et al 2010]. Also, Eguileor et al (2001) has suggested that salivary glands in the aphid parasitoid Aphidius ervi might be functioning as an excretory tissue.…”
Section: Relationship Between Malpighian Tubules and Salivary Glandsmentioning
confidence: 86%
“…With the explosion of high throughput techniques, the transcriptome, proteome and even metabolome of Malpighian tubules from several species are being characterized [Esquivel et al 2014, Silva et al 2015, Dow and Davies 2006, Zhong et al 2013. These characterizations are consistently identifying molecules involved in detoxification as well as immunity.…”
Section: Overview Of Malpighian Tubulesmentioning
confidence: 99%
See 1 more Smart Citation
“…11,27 Genomic and proteomic analysis studies may elucidate their intracellular signaling mechanisms, 81,82 regulating the immune response, 83 in addition to other functions of MTs, as their relationship with the bioluminescence mechanism in some insects. 84,85 The results indicate that MTs can be used for the evaluation of biomarkers, at the cellular level, in toxicological studies, especially studies done with sublethal doses and concentrations of chemicals. The various roles played by MTs reflect the interactions that organisms have with the environment in which they live.…”
Section: Closing Argumentsmentioning
confidence: 98%